The Development of Anti-Hoax Digital Comics for the 2024 Presidential Election: A Research-Based Approach Reflecting Surah Al-Hujurat Verse 6 - Nina; Triyanto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
The 2024 Indonesia presidential election underwent the possibility of disseminating false information. Digital comics are deemed useful in combating misinformation due to their proximity to the younger generation. The research aims to develop a digital comic to raise public awareness about the dangers of spreading hoax news in the 2024 Presidential Election using the principles of Surah Al-Hujurat verse 6. Employing the ADDIE analysis model, this research collects main data from first-time voters between the ages of 17-25 who are active on social media. The research uses the 5W+1H framework in analyzing data. This strategy is frequently employed to gather data and assess an issue, enabling the formulation of an appropriate solution. This research finds that 45 respondents who have read the comic reveal that 89% comprehend the storyline; 96% believe the narrative accurately reflects the current political climate in Indonesia; 98% feel that reading this comic enhances their critical evaluation of news; 93% assert that the comic educates about misinformation in the lead-up to elections; and 100% express interest in and recommend this digital comic to friends or relatives.